Ultrasonographically guided percutaneous transhepatic liver biopsy after pediatric liver transplantation. (11th March 2021) - Sanada, Yukihiro; Sakuma, Yasunaru; Onishi, Yasuharu; Okada, Noriki; Yamada, Naoya; Hirata, Yuta; Miyahara, Go; Katano, Takumi; Horiuchi, Toshio; Omameuda, Takahiko; Ogaki, Keiko; Otomo, Shinya; et al.
Abstract: Background: Complications associated with ultrasonographically guided percutaneous transhepatic liver biopsy (PTLB) after liver transplantation (LT) have been rarely reported, and there is no consensus about its safety. We retrospectively reviewed the safety and outcomes of PTLB after pediatric LT. Methods: Between January 2008 and December 2019, 8/1122 (0.71%) pediatric patients who underwent ultrasonographically guided PTLB after LT developed complications. The median age at PTLB was 7.8 years (range 0.1–17.9). Grafts included left lobe/left lateral segment in 1050 patients and others in 72. PTLB was performed using local anesthesia±sedation in 1028 patients and general anesthesia in 94. Results: Complications after PTLB included acute cholangitis in 3 patients, sepsis in 2, respiratory failure due to over‐sedation in 1, subcapsular hematoma in 1, and intrahepatic arterioportal fistula in 1. The incidence of complications of PTLB in patients with biopsy alone and those with simultaneous interventions was 0.49% and 3.19%, respectively ( p  = .023). Patients who developed acute cholangitis, respiratory failure, subcapsular hematoma, and arterioportal fistula improved with non‐operative management. Of two patients with sepsis, one underwent PTLB and percutaneous transhepatic portal vein balloon dilatation and developed fever and seizures the following day. Sepsis was treated with antibiotic therapy. Another patient who underwent PTLB and exchange of percutaneous transhepatic biliary drainage catheter developed fever and impaired consciousness immediately. Sepsis was treated with antibiotic therapy, mechanical ventilation, and continuous hemofiltration. Conclusions: Percutaneous transhepatic liver biopsy after pediatric LT is safe. However, combining liver biopsy with simultaneous procedures for vascular and biliary complications is associated with an increased risk of complications.